Reading price charts bar by bar : the technical analysis of price action for the serious trader - Brooks, Al, 1952- (Wiley, 2009)
While new technology and complicated theories promise to take your trading to "the next level," the truth is that long-term success in this field is rooted in simplicity. That's why Al Brooks has created Reading Price Charts Bar by Bar. With this book, Brooks'a technical analyst for Futures magazine and an independent trader'demonstrates how applying price action analysis to chart patterns can help enhance returns and minimize downside risk. Along the way, you'll discover the importance of understanding every bar on a price chart, why particular patterns are reliable setups for trades, and how to locate entry and exit points as markets are trading in real time. Throughout these pages, some of the most useful tools for deciphering price action are covered in detail, including: - Trendlines and trend channel lines - Prior highs and lows - Breakouts and failed breakouts - The size of bodies and tails on candles - The relationship between current bars to prior bars - And much more Learning what the market is telling you can be difficult, but with the right approach, you can achieve this goal and capture consistent profits in the process. Reading Price Charts Bar by Bar has all the information you need to succeed at this endeavor and will put you in the best position possible to make the most of your time in today's turbulent markets. Praise for Reading Price Charts Bar by Bar "Al Brooks has written a book every day trader should read. On all levels, he has kept trading simple, straightforward, and approachable. By teaching traders that there are no rules, just guidelines, he has allowed basic common sense to once again rule how real traders should approach the market. This is a must-read for any trader that wants to learn his own path to success." 'Noble DraKoln, founder ofwww.SpeculatorAcademy.com and author of Trade Like a Pro and Winning the Trading Game "Al Brooks is a trader's trader. He understands the focused energy it takes to be successful at trading and works long, hard hours in front of the computer screen to beat the markets. In his first trading book, he outlines, selflessly, his strategy step by step. A doctor and educator in his previous life, he uses his eye for detail and transfers lessons he learned in training himself on the art of trading to the written page. For those who are willing to delve into the details of day trading and dedicate the time and energy to do it seriously and most likely profitably, Al Brooks's book Reading Price Charts Bar by Bar, is a must-read." 'Ginger Szala, Publisher and Editorial Director, Futures magazine